Impact Analysis of UNESCO Recognition of Sangiran Site: Between Economic Growth and Cultural Preservation - Kim Maiko; Feni Amalia Rahmayatni; Arie Kusuma Paksi (Interdisciplinary Social Studies, 2025)
The Sangiran site in Central Java, recognized as a UNESCO World Heritage Site in 1996, is a pivotal paleontological location renowned for its prehistoric fossils. While this designation has spurred economic growth through tourism, it has also introduced challenges such as cultural commodification and spatial inequality. This study examines the dual impact of UNESCO recognition on Sangiran, focusing on the tensions between economic development and cultural preservation. Using a qualitative approach and the Cultural Political Economy of Heritage (CPEH) framework, the research analyzes secondary data from official reports, scholarly articles, and media to explore these dynamics. Findings reveal that while tourism has boosted local incomes, benefits are unevenly distributed, favoring communities near the museum cluster. Additionally, cultural practices risk being simplified for tourist consumption, threatening intangible heritage. Governance remains top-down, marginalizing local voices in decision-making. The study concludes that UNESCO status presents both opportunities and risks, necessitating inclusive policies to balance economic gains with cultural integrity. Key recommendations include enhancing community participation, equitable benefit-sharing, and safeguarding intangible heritage.